2015
DOI: 10.1007/978-3-662-46943-9_17
|View full text |Cite
|
Sign up to set email alerts
|

Clinical ECG Assessment

Abstract: With the adoption of the ICH E14 guidance, the thorough QT/QTc (TQT) study has become the focus of clinical assessment of an NCE's effects on ECG parameters. The TQT study is used as a guide to the liability of a drug to cause proarrhythmias on the basis of delayed cardiac repolarization. Around 300 TQT studies have been performed since 2005 and through interactions between sponsors and regulators, especially FDA's Interdisciplinary Review Team (IRT) for QT studies. These studies can today be performed more ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 109 publications
0
5
0
Order By: Relevance
“…ECGs were extracted and measured by a central ECG laboratory (iCardiac Technologies, Rochester, New York) using the high‐precision QT technique, as previously described . This technique was chosen, as it has been demonstrated that it results in substantially lower variability of change‐from‐baseline QTc (∆QTc) and therefore improves the power to exclude small QT effects . The QT interval was heart rate–corrected using Fridericia's formula (QTcF = QT/RR 1/3 ), and a subject‐specific correction using all QT/RR pairs from the full 24‐hour baseline recording was applied as follows: based on the QT/RR pairs from each individual subject, the QTcI correction factor was derived from linear regression modeling: log(QT) = log(a) + b × log(RR).…”
Section: Methodsmentioning
confidence: 99%
“…ECGs were extracted and measured by a central ECG laboratory (iCardiac Technologies, Rochester, New York) using the high‐precision QT technique, as previously described . This technique was chosen, as it has been demonstrated that it results in substantially lower variability of change‐from‐baseline QTc (∆QTc) and therefore improves the power to exclude small QT effects . The QT interval was heart rate–corrected using Fridericia's formula (QTcF = QT/RR 1/3 ), and a subject‐specific correction using all QT/RR pairs from the full 24‐hour baseline recording was applied as follows: based on the QT/RR pairs from each individual subject, the QTcI correction factor was derived from linear regression modeling: log(QT) = log(a) + b × log(RR).…”
Section: Methodsmentioning
confidence: 99%
“…The maximum, baseline-adjusted and vehicle-adjusted (ΔΔ)QTc (ms) was used as the primary response endpoint for human TQT studies and maximum, baseline-adjusted (Δ)QTc (ms) for in vivo QTc studies (Anonymous, 2005a;Darpo, 2010;Stockbridge et al, 2012;Darpo, 2015). A positive response in the in vivo QTc assay was defined by the sponsor's claim of a significant drug-related effect.…”
Section: Dichotomous Endpoints For Assays and Concordance Assessmentsmentioning
confidence: 99%
“…Moreover, there were no clinically significant effects of futibatinib on heart rate, other ECG parameters, or ECG morphology, and a concentration‐dependent effect on QTcF prolongation between the 2 doses of futibatinib was not apparent. Overall, the study met the criteria for a negative thorough QT/QTc study per ICH guidance 11–14 …”
Section: Discussionmentioning
confidence: 99%
“…To characterize the clinical effects of futibatinib on cardiac repolarization and to assess its proarrhythmic potential, we conducted a randomized, controlled, double‐blind, thorough QT/QTc, phase 1 study in healthy subjects following established guidelines 11–14 . The primary objective of this study was to assess the impact of the therapeutic and supratherapeutic futibatinib doses of 20 and 80 mg, respectively, on the QT interval corrected for heart rate with the Fridericia formula (QTcF) compared with placebo.…”
mentioning
confidence: 99%